Effects of compression stockings on lower-limb venous and arterial system responses to prolonged sitting: A randomized cross-over trial. (August 2021) - Horiuchi, Masahiro; Stoner, Lee
Exposure to prolonged sitting increases blood pooling and the risk of lower-extremity vascular arterial and venous complications, including deep vein thrombosis. Compression garment stockings (CGS) may prevent pooling, thereby mitigating the associated vascular complications. Three aims were addressed: (i) does use of CGS help to prevent blood pooling; (ii) does blood pooling correlate with decreased stroke volume; and (iii) does use of CGS preserve leg arterial flow-mediated dilation and reactive hyperemia response. Twenty inactive participants (22 ± 4 years, 30% female, 22.1 ± 2.0 kg/m 2 ) were randomized to sit for 3 hours with (CGS) and without use of CGS. Blood pooling was determined using medial gastrocnemius total hemoglobin. Stroke volume was estimated using finger photoplethysmography, respectively. Macrovascular and microvascular function were measured using popliteal artery flow-mediated dilation and reactive hyperemia, respectively. In response to 3 hours of sitting: (i) there was an interaction effect for total hemoglobin ( p < 0.001); the condition without use of CGS increased 10.5% (95% CI: 6.7 to 14.3) and CGS increased 4.3% (95% CI: 0.1 to 7.7); (ii) blood pooling was negatively associated with stroke volume ( r = −0.58, 95% CI: −0.68 to −0.45); (iii) reactive hyperemia and flow-mediated arterial dilation was impaired after prolonged sitting, and use of CGS was not associated with attenuation of this impairment. Use of CGS decreases blood pooling but does not preserve arterial macrovascular and microvascular responses to prolonged sitting. Further study is warranted to determine whether CGS has additive benefits when combined with sitting interruption strategies.